2013
DOI: 10.1177/1071100713483117
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Foot and Ankle Outcome Score in Adult Acquired Flatfoot Deformity

Abstract: Level II, prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 27 publications
7
74
0
1
Order By: Relevance
“…In our assessment of the content validity, or relevance, of the FAOS from the patient's perspective, we found that the FAOS was deemed relevant in all subscales with the exception of ADLs. Though the ADL subscale showed a trend toward relevance with a preoperative and postoperative average of 1.9, this finding is consistent with those found in recent FAOS validation studies for hallux valgus and flatfoot deformity [5,11]. Though it is, however, important to note that in the validation of Roos et al of the FAOS for ankle ligament reconstruction all subscales were deemed relevant [18].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our assessment of the content validity, or relevance, of the FAOS from the patient's perspective, we found that the FAOS was deemed relevant in all subscales with the exception of ADLs. Though the ADL subscale showed a trend toward relevance with a preoperative and postoperative average of 1.9, this finding is consistent with those found in recent FAOS validation studies for hallux valgus and flatfoot deformity [5,11]. Though it is, however, important to note that in the validation of Roos et al of the FAOS for ankle ligament reconstruction all subscales were deemed relevant [18].…”
Section: Discussionsupporting
confidence: 85%
“…This broad range does carry a concern regarding the ability of the FAOS to provide consistent assessment in both the immediate and long term. However, this concern is tempered by our reliability findings being consistent with those proven for the FAOS validation for both hallux valgus and flatfoot deformity with each also found the FAOS reliable on all subscales [5,11].…”
Section: Discussionsupporting
confidence: 85%
“…Another thing to consider is improving the frequency of reporting sport-specific subscales of already validated questionnaires. The AOFAS[35], FAOS[59,153,154] and Thermann[43] scores include sports and activity sub-scales but these subscales are infrequently reported. Finally, though all terms implying sports participation of activity were included in this systematic review, it was noted that a number of different terms were used in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study, therefore, was to evaluate the relationship between postoperative hindfoot alignment following an MCO for stage II AAFD and patient outcomes using the Foot and Ankle Outcome Score (FAOS), previously validated for patients with flatfoot deformity. 17 Our hypothesis was that patient outcomes would be highest in the cohort that was corrected to a mild varus hindfoot alignment postoperatively.…”
Section: Introductionmentioning
confidence: 99%